Conference Report: Emerging technology for bioanalysis in the next decade. (November 2012) - DeMuth, James E; Ji, Qin C; Booth, Brian P; Fluhler, Eric N; Greathead, Roger; Ho, Stacy; Stubbs, R John; Turk, Douglas J
This University of Wisconsin School of Pharmacy bioanalytical conference is presented each year by the Extension Services in Pharmacy, the professional development department within the School. The purpose of this 4-day conference is to provide an educational forum to discuss issues and applications associated with the analysis of xenobiotics, metabolites, biologics and biomarkers in biological matrices. The conference is designed to include and encourage an open exchange of scientific and methodological applications for bioanalysis. To increase the interactive nature of the conference, the program was a mixture of lectures, poster sessions, round table discussions and workshops. This article summarizes the presentations at the 13th Annual Conference.